Korzenie i źródło. Hannah Arendt i Roger Scruton o genezie totalitaryzmu (w Conradowskim kontekście) - Ratajczak, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The three authors’ community of thought can be noticed in the analysis of their attitude towards the Nietzschean concept of ressentiment. Arendt observed the ressentiment and contempt of educated people towards society that grew since the mid-eighteenth century. In Conrad’s prose, a specific culmination of such emotions can be found in the character of the Professor in The Secret Agent novel. Scruton understood a totalitarian state as an institutionalised form of executing ressentiment. Another crucial common point of reference for the three authors was the issue of authority.Scruton reminded us that society exists thanks to authority. The opposite of ressentiment seems to be affirmation, while revolutionary aims of radical revaluation can be contrasted with conservatism as a philosophy of attachment to what is valuable. One can understand Conrad’s concept of loyalty as such.